2020
DOI: 10.1186/s40779-020-00277-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in severely injured patients admitted to the intensive care unit

Abstract: Background Our objective was to identify possible associations between clinical and laboratory variables and the risk of developing acute kidney injury (AKI) in severely injured patients admitted to the intensive care unit (ICU) for whom creatine kinase (CK) levels were available. Methods For this retrospective observational study, we analyzed adult trauma patients admitted to the ICU from 2011 to 2015 at Fundación Valle del Lili (FVL) University Hospital. Our primary outcome was the incidence of AKI. Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that the mortality rate among AIS patients with AKI is three times higher than that among those without AKI (16). In addition, for intensive care patients, occurrence of AKI will increase their mortality (17). Therefore, it is particularly important to screen for AKI-related risk factors among critical patient with AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the mortality rate among AIS patients with AKI is three times higher than that among those without AKI (16). In addition, for intensive care patients, occurrence of AKI will increase their mortality (17). Therefore, it is particularly important to screen for AKI-related risk factors among critical patient with AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is one of the most common organ failures in patients hospitalized in intensive care units (ICUs) [ 1 ]. The incidence varies from 5% to 50% depending on the literature and is associated with a mortality rate of up to 50% [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%